A pioneering critic of Alexander von Humboldt’s inventions: Francisco José de Caldas - Gómez Gutiérrez, Alberto (HiN - Alexander von Humboldt in the Net. International Review for Humboldt Studies, 2024)
Abstract Alexander von Humboldt has been praised and criticized throughout history depending on different readings and interests. The account of his encounters during his American voyage can shed light on the foundations for criticism and praise. This essay addresses the critical attitude of botanist and astronomer Francisco José de Caldas towards Alexander von Humboldt in years 1801 to 1803. Resumen Alexander von Humboldt ha sido exaltado y criticado a través de la historia en función de lecturas e intereses diversos. La relación de sus encuentros en el curso de su viaje americano puede dar luces sobre el fundamento de las críticas y los elogios. Este ensayo aborda la actitud crítica del botánico y astrónomo Francisco José de Caldas hacia Alexander von Humboldt en los años 1801 a 1803. Résumé Alexander von Humboldt a été loué et critiqué tout au long de l’histoire, en fonction des lectures et des intérêts particuliers. Le récit de ses rencontres lors de son voyage en Amérique peut éclairer les fondements des critiques et des éloges. Cet essai traite de l’attitude critique du botaniste et astronome Francisco José de Caldas à l’égard d’Alexander von Humboldt dans les années 1801 à 1803.